Social And Psychological Factors Influencing The Development Of Interpersonal Activity In Preschool Children (Texas Journal of Multidisciplinary Studies, 2026)
Early childhood is considered a critical period for the development of interpersonal relationships and social behavior. The formation of interpersonal activity during the preschool years plays a significant role in shaping children's communication skills, cooperation, and emotional intelligence. This study examines the social and psychological factors that influence the development of interpersonal activity in preschool children. The research focuses on the influence of family environment, peer relationships, and preschool educational conditions on children's social behavior. Quantitative and qualitative methods were used, including observation, behavioral assessment, and statistical analysis. The findings show that supportive educational environments and positive social interactions significantly enhance interpersonal competence in preschool children.